RETRACTED: MiRNA-200b Regulates RMP7-Induced Increases in Blood-Tumor Barrier Permeability by Targeting RhoA and ROCKII - Ma, Teng; Xue, Yi-xue (Frontiers in Molecular Neuroscience, 2016)
The primary goals of this study were to investigate the potential roles of miR-200b in regulating RMP7-induced increases in blood-tumor barrier (BTB) permeability and some of the possible molecular mechanisms associated with this effect. Microarray analysis revealed 34 significantly deregulated miRNAs including miR-200b in the BTB as induced by RMP7 and 8 significantly up-regulated miRNAs in the BTB by RMP7. RMP7 induced tight junction (TJ) opening of the BTB, thereby increasing BTB permeability. Associated with this effect of RMP7 was a decrease in miR-200b expression within the human cerebral microvascular endothelial cells line hCMEC/D3 (ECs) of the BTB. Overexpression of miR-200b inhibited endothelial leakage and restored normal transendothelial electric resistance values. A simultaneous shift in occludin and claudin-5 distributions from insoluble to soluble fractions were observed to be significantly reduced. In addition, overexpression of miR-200b inhibited the relocation of occludin and claudin-5 from cellular borders into the cytoplasm as well as the production of stress fiber formation in GECs (ECs with U87 glioma cells co-culturing) of the BTB. MiR-200b silencing produced opposite results as that obtained from that of the miR-200b overexpression group. Overexpression of miR-200b was also associated with a down-regulation in RhoA and ROCKII expression, concomitant with a decrease in BTB permeability. Again, results which were opposite to that obtained with the miR-200b silencing group. We further found that miR-200b regulated BTB permeability by directly targeting RhoA and ROCKII. Collectively, these results suggest that miR-200b’s contribution to the RMP7-induced increase in BTB permeability was associated with stress fiber formation and TJ disassembly as achieved by directly targeting RhoA and ROCKII.